The impact of having children on domain-specific life satisfaction: A quasi-experimental longitudinal investigation using the Socio-Economic Panel (SOEP) data - Michael D. Krämer; Joseph L. Rodgers (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
Longitudinal studies have documented improvements in parents' life satisfaction due to childbearing, followed by postpartum adaptation back to baseline. However, the details underlying this process remain largely unexplored. Based on past literature, set-point theory, and results from an exploratory sample, we investigated empirically how first childbirth affected satisfaction with specific domains of life. In a preregistered study, we compared parents with matched childless respondents in their trajectories of life satisfaction, and also satisfaction with family life, health, sleep, work, housework, leisure, dwelling, household income, and personal income. First-time parents and childless respondents were matched in a procedure combining exact and propensity score matching. Using the population-representative German SOEP data (N = 3,370), longitudinal multilevel models revealed heterogeneous effects of childbirth on different domains of satisfaction: Both mothers' and fathers' satisfaction with family life increased temporarily in a similar fashion to life satisfaction before going back to baseline within five years after childbirth. However, only mothers experienced drastic losses to satisfaction with sleep and satisfaction with personal income. For the remaining domains, parents' satisfaction largely resembled that of the matched childless respondents. These divergent domain trajectories underscore the need for multivariate analyses in life satisfaction research.'
Keywords: 330; Life Satisfaction; Satisfaction Domains; Childbirth; Parents; Propensity Score Matching